USE OF TAM FOR EVALUATION OF INTERNSHIP INFORMATION SYSTEM - Arif Setia Sandi A; Bambang Soedijono; Asro Nasiri (LPPM STMIK Pringsewu, 2022)
This study aims to evaluate the internship information system at a Vocational High School. To achieve this goal, it is necessary to perform statistical analysis and calculations on the influence of the relationship between each variable in the Technology Acceptance Model (TAM) with the addition of one external variable, namely self-efficacy variable. The approach used in this research is quantitative. The source of the data used is primary data, derived from the users of the internship information system through a questionnaire containing eighteen questions with five alternative answers using a Likert scale as a point determination. Respondents targeted in this study amounted to 202 respondents, but one other thing was constrained, only 180 respondents filled out the questionnaire. refers to the analysis obtained using WarpPLS, data obtained that: (1) the convenience factor has an influence on the benefits, in using the information system, (2) the use benefit factor has a real influence on the intensity and use of the information system, (3) the attitude of use has influence on the intensity of the use of information systems, (4) the intensity has an effect on the use of information systems in real or implementation. (5) self-efficacy has an influence on the ease of use of information systems.